Silver Economy sebagai Solusi Inklusif Menghadapi Aging Population di Era Industri 4.0 - Amelia, Ananda Tri (Samsara Institute Publisher, 2025)
The economic paradigm shift due to the Industrial Revolution 4.0, characterized by the integration of digital technology, automation and artificial intelligence (AI), is happening significantly. This is also accompanied by the phenomenon of an aging population, which is estimated to reach 2.1 billion by 2050, and is an important challenge facing Indonesia. In this context, the silver economy approach is considered relevant and inclusive in order to optimize the role and potential of the elderly in the era of the Industrial Revolution 4.0. Silver economy sees the elderly not as a vulnerable and dependent group, but as subjects who can still be empowered, given skills, and given access to appropriate technology. This is in line with the concept of Human Capital and Harrod-Domar's modernization theory, which focuses on the importance of the quality of human resources for the achievement of development. This study found that the silver economy can be a solution for demographic transformation, if there is synergy between the government and the private sector, namely through training, policy support, and access to available and appropriate technology. With this approach, Indonesia's aging population is no longer a problem, but a potential that can be maximized for a more independent, prosperous, superior, and inclusive society.